Factors associated with metabolic syndrome among adult residents in Dalian: a nested case-control study - Rong, Rong; Luo, Lan; Li, Xinyu; Gao, Zhengnan (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate risk factors for metabolic syndrome (MS) among adult residents in Dalian, Liaoning Province, China, using a nested case-control design.MethodsAdult participants from Dalian who took part in both baseline and follow-up phases of the Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal (REACTION) Study were evaluated through standardized questionnaires, physical examinations, and biochemical analyses. A total of 536 individuals diagnosed with MS were matched in a 1:4 ratio to 2,144 controls based on comparable demographic and clinical characteristics. Group differences were assessed via t-tests, rank sum tests, and χ² tests. Multivariate conditional logistic regression was applied to identify risk factors for MS.Results(1) The case group demonstrated significantly higher values for body weight(67.42 ± 9.77 vs. 62.39 ± 9.31, P<0.001), body mass index (BMI) (25.99 ± 3.36 vs 24.00 ± 3.14, P<0.001), hip circumference (HC) (100.72 ± 6.47 vs 97.84 ± 6.38, P<0.001), homeostatic model assessment for insulin resistance (HOMA−IR) (2.27 ± 1.19 vs 1.70 ± 0.92, P<0.001),total cholesterol (TC) (5.54 ± 1.08 vs 5.40 ± 0.97, P=0.003), low-density lipoprotein cholesterol (LDL-C) (3.38(2.79,3.96) vs 3.17(2.67,3.71), P<0.001), alanine aminotransferase (ALT) (16.00(13.00,21.00) vs 15.00(11.00,19.00), P<0.001), gamma-glutamyl transferase (GGT) (22.00(17.00,33.00) vs 18.00(14.00,27.00), P<0.001), serum uric acid (UA) (303.50(263.00,355.00) vs 281.00(245.00,325.00), P<0.001), glycosylated hemoglobin (HbA1c) (5.93 ± 0.88 vs 5.75 ± 0.68, P<0.001), and fasting insulin (FINS) (8.05(5.90,10.70) vs 6.15(4.60,8.30), P<0.001) (2). Higher prevalence rates were also observed for coronary heart disease (4.86% vs 2.87%, P=0.020), habitual snoring (66.53% vs 54.96%, P<0.001), and consumption of fresh juice (17.99% vs 13.12%, P=0.004), beef and mutton (78.42% vs 74.07%, P=0.038), and soda the case group (20.15% vs 16.32%, P=0.049). Meanwhile, lower participation in aerobic activities(1.20% vs 2.92%, P=0.030) and shorter average daily sleep duration (7.55 ± 1.02 vs 7.69 ± 1.17, P=0.028) were noted in the case group (3). Regression analysis identified longer average daily sleep duration as a protective factor(OR=0.844, 95%CI: 0.761-0.936, P=0.001), while fresh juice intake(OR=1.846, 95%CI: 1.315-2.592, P<0.001), beef and mutton consumption(OR=1.282, 95%CI:1.007-1.632, P=0.044), LDL-C(OR=1.409, 95%CI: 1.245-1.595, P<0.001), GGT(OR=1.004, 95%CI: 1.001-1.008, P=0.017), UA(OR=1.005, 95%CI: 1.003-1.007, P < 0.001), HOMA-IR (OR=1.464, 95%CI: 1.313-1.633, P < 0.001), HC(OR=1.030, 95%CI: 1.007-1.053, P = 0.009), and BMI(OR=1.118, 95%CI: 1.064-1.174, P < 0.001)were significant risk factors.ConclusionLDL-C, GGT, UA, HOMA-IR, HC, BMI, daily sleep duration, and consumption of beef and mutton, and fresh juice were strongly associated with the incidence of MS among adult residents in Dalian.